Application of dual-solvent extraction for separating a low-temperature coal tar: A detailed experimental and quantum chemical study. (15th February 2023) - Ma, Zhi-Hao; Li, Sheng; Guo, Chun; Dong, Xue-Qian; Wang, Jin-Hu; Li, Min; Guo, Xian-Hou; Xu, Mei-Ling; Cong, Xing-Shun; Zong, Zhi-Min; Wei, Xian-Yong
Graphical abstract: The enrichment of alkanes, arenols, and arenes from a low-temperature coal tar was subjected to extraction kinetics, molecular composition, functional group distribution, separation mechanism, and molecular simulation analysis. Highlights: A low-temperature coal tar was enriched through dual-solvent systems. The extracts were elucidated from the molecular level, content, and functional group. Separation driving force was clarified combining theoretical and quantum chemistry. Abstract: A low-temperature coal tar (LTCT) was separated by dual-solvent systems to realize its value-added utilization. Cumulative extract yield (CEY) versus time, extraction kinetics at different stages, extracted composition, and functional group distribution were intensively studied using nonlinear fitting, linear fitting, gas chromatograph/mass spectrometer (GC/MS), and Fourier transform infrared (FTIR) spectrometer, respectively. The relationship between CEY and time conformed to logistic model, and the determination coefficient is 0.97. Among the 3 extraction stages, the slope of the kinetic fitting curves in their extraction stage using petroleum ether (the first 3 runs) in the highest extract yield is 7.5 and 5 times that using methanol and carbon disulfide extraction stage, respectively. Alkanes, arenols, and arenes can be enriched into petroleum ether, methanol, and carbon disulfide, respectively. A total of 314 compounds detected in the LTCT and extracts with GC/MS were subdivided into 85 group components. The result of FTIR analysis is consistent with that of GC/MS. Separation mechanism was expounded by theory analysis and quantum chemistry from hydrogen bonds (O-H··· O) and van der Waals force. Quantum chemical calculations show that the attraction of alkane, alkene, anthracene, and naphthalene with n -hexane or carbon disulfide is mainly dispersive interaction, while the attraction of methanol with phenols is mainly electrostatic interaction. Although the bond length of O-H··· O formed between methanol and phenols is 2/3 of that of C-H··· O, and the bond angle is ca . 45° larger, the binding energy is 9 times that of the latter, indicating that the main hydrogen bonds are O-H··· O. In summary, dual-solvent extraction has considerable potential to separate alkanes, arenols, and arenes from the LTCT.